1984
DOI: 10.1111/j.1469-8986.1984.tb02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rhythm Control During Sleep

Abstract: Heart rate (HR) rhanRcs during sleep were analyzed, with the aid of a minicomputer, for a group of 20 healthy subjects. In stages 1, 2, 3, and 4, HR decreased against a background of increasing respiratory arrhythmia. REM sleep was characterized by increased HR and decreased respiratory arrhythmia. HR changes during sleep were dependent on the subject's initial autonomic HR control level. The evidence from 3 healthy subjects, who were studied under baseline conditions, propranolol (a sympatholytic agent), atro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
69
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(83 citation statements)
references
References 16 publications
14
69
0
Order By: Relevance
“…This algorithm was modified to achieve an automatic, continuous, and multisignal analysis to meet the needs of sleep studies. With the use of such techniques, our previous studies demonstrated that QS was accompanied by an intense vagal function but an attenuated sympathetic function compared with AW (28,29), and these findings were compatible with earlier reports (1,30). The changes of sleep-related autonomic functions associated with spontaneous hypertension, however, have not yet been systemically investigated.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This algorithm was modified to achieve an automatic, continuous, and multisignal analysis to meet the needs of sleep studies. With the use of such techniques, our previous studies demonstrated that QS was accompanied by an intense vagal function but an attenuated sympathetic function compared with AW (28,29), and these findings were compatible with earlier reports (1,30). The changes of sleep-related autonomic functions associated with spontaneous hypertension, however, have not yet been systemically investigated.…”
Section: Discussionsupporting
confidence: 87%
“…The data under sleep, however, have been relatively less reported and may be different from those under anesthesia or AW. It has been reported that sleep triggers a series of changes in autonomic functions (1,(28)(29)(30), and the changes may be very vigorous (28,29). Because most of the previous studies regarding the ANS have been carried out for a relatively short time during the daytime, which is the time when rats sleep, it is in fact difficult to quantify the autonomic changes accurately without a classification of sleep-wake states.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition times for wakefulness, REMS and NREMS largely overlapped. Furthermore, a circadian factor is probably minor because VHR is highly sleep stage dependent (Zemaityte et al, 1984;Raetz et al, 1991;Vanoli et al, 1995;Pivik et al, 1996;Brandenberger et al, 2001;Viola et al, 2002). For instance, individual profiles revealed abrupt HR increases in each transition from deeper sleep to lighter sleep or awakening (Viola et al, 2002).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…There is a decrease in heart rate and this decrease may be seen even prior to onset of stage 1 (Pivik and Busby, 1996) although the heart rate changes during drowsiness are not great (Torsvall and Akerstedt, 1987;Welch and Richardson, 1973). The heart rate decrease during the sleep onset period appears to relate to decreased sympathetic and increased parasympathetic tone (Zemaityte and Varoneckas, 1984). There are also physiologic changes in respiration.…”
Section: Physiological Changes Other Than Eegmentioning
confidence: 99%